2021
DOI: 10.1080/0886022x.2021.1979040
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circular RNA expression profiles in renal fibrosis induced by obstructive injury

Abstract: Introduction Advancing renal fibrosis is the common histopathological feature of chronic obstructive nephropathy, representing the final pathway of nearly all chronic and progressive nephropathies. Increasing evidences suggest that circular RNAs (circRNAs) are crucial regulatory molecules present at virtually every level of the cellular pathophysiological process. Nonetheless, there are a few evidences for the role of circRNAs in renal fibrosis induced by obstructive nephropathy. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…At present, there are few research articles on the relationship between circRNA and urethral stricture. The existing literature mainly focuses on renal fibrosis 20 , 27 . Other studies have found that circRNA is related to the mechanism of keloid formation 29 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are few research articles on the relationship between circRNA and urethral stricture. The existing literature mainly focuses on renal fibrosis 20 , 27 . Other studies have found that circRNA is related to the mechanism of keloid formation 29 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA (circRNA) is a new endogenous non-coding RNA that has attracted research interest 19 . Previous studies show that circRNA is involved in many disease processes, including renal and liver fibrosis 20 , 21 . In the reports of fibrosis-related diseases, like myocardial fibrosis 22 , diabetic nephropathy 23 and pulmonary fibrosis 24 , it has been revealed that circRNA acts as a molecular sponge, which can isolate miRNA molecules and prevent the mechanism of targeting mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…This model has certain advantages in that it is a nonuremic normotensive disorder in the absence of any apparent inflammatory or toxic insult to the kidneys [ 88 ]. Moreover, the UUO model of kidney injury is also a good model for studying the pathophysiology of renal fibrosis [ 89 , 90 , 91 , 92 , 93 ]. Therefore, the UUO model of kidney injury may closely mimic the underlying pathophysiology of human obstructive kidney injury [ 94 , 95 ].…”
Section: Protective Roles Of α-Lipoic Acid (Ala) In Kidney Injurymentioning
confidence: 99%
“…These findings mirror those in other mammalian models, with 605 circRNAs upregulated and 745 circRNAs downregulated in a murine UUO model. Gene Ontology analysis showed that many of these circRNAs were involved in pathways relating to cell apoptosis and p53 signalling [ 96 ]. In a smaller study, mmu_circ_30032 expression was upregulated in the murine UUO model, promoted by the activation of the p38-MAPK pathway, resulting in the deposition of type I collagen, type III collagen, and fibronectin via miR-96-5p [ 57 ].…”
Section: Circrna Expression In Aki Due To Urinary Tract Obstructionmentioning
confidence: 99%